Enhanced Recovery After Surgery program with dexamethasone administration for major head and neck surgery with free tissue transfer reconstruction: initial institutional experience. (3rd July 2018) - Imai, Takayuki; Kurosawa, Koreyuki; Yamaguchi, Kayo; Satake, Naoko; Asada, Yukinori; Matsumoto, Ko; Morita, Sinkichi; Saijo, Satoshi; Aoi, Jiro; Fujii, Keitaro; Kishimoto, Kazuhiro; Goto, Takahiro; et al.
Abstract: Objectives: Enhanced Recovery After Surgery (ERAS) protocols promote recovery after various invasive surgeries. Likewise, preoperative glucocorticoid administration can reduce complications after some surgeries. However, the effects of ERAS protocols and glucocorticoid administration in patients undergoing major surgery for head and neck cancer have not been well described. The aim of this study was to evaluate the effect of an ERAS protocol with preoperative glucocorticoid administration in major surgery for head and neck cancer. Methods: This retrospective study included 28 patients who underwent major head and neck surgery with free tissue transfer reconstruction at our institution from September 2016 to May 2017, after implementation of an ERAS protocol with preoperative glucocorticoid administration. Outcomes in that group were compared with those in a control group that underwent surgery from January 2015 to September 2016, before implementation of the protocol. Results: Analysis revealed significantly less body weight fluctuation, lower C-reactive protein levels, higher albumin levels, and lower body temperature in the ERAS group than in the control group postoperatively. Conclusions: Patients undergoing major surgery for head and neck cancer who were treated with the ERAS protocol and preoperative glucocorticoid administration had evidence of better hemodynamic stability and less inflammatory response than control patients.